Immunization Coverage in a Rural Area - Abdul Rehman Shaikh, Fazal Mehmood,Maqsood Hayat (Journal of Rawalpindi Medical College, 2016)
Background: To assess the immunization status of children less than 2 years of age. The impact of mother’s education, presence of health workers in the area and gender on immunization status was studied. Methods: In this descriptive cross-sectional study, carried out in slums, nomads and other areas of a union council in Islamabad,a total of 768 children were recruited for study less than 2 years of age. Data collection was carried out by using a structured performa, interviewing parents of children for dates on vaccination cards looking at the BCG scar mark. Cluster sampling technique was adopted and a total of 96 clusters were taken in whole of the area. Results: Out of total 786 study participants 98% received some form of immunization and 2% received no immunization at all. 52% were males whereas 48% were females. Among the males the immunization status distribution was 80% fully immunized, 17% partially immunized and 3% not immunized against any antigen. In the females 80% were fully immunized, 19% partially immunized and 1% not immunized against any antigen. In the children age group 15 months and above who completed their age for EPI schedule, 81% were fully immunized, 17% partially immunized and 2% were not immunized against any EPI antigen. The valid coverage (vaccination card only) of these vaccines by antigen was highest in penta1/pneumococcal1/opv1 of 86% and lowest in measles2 which was 75%. The coverage of antigens by card plus history was highest of 97% in BCG and penta1/pneumococcal1/opv1 and lowest of 88% in measles2. Lady health workers covered areas had a better coverage rate ( 99%). Conclusion:EPI coverage in union council Islamabad is quite well established. The immunization coverage status for male and female children is equal. The surveillance and monitoring system is well designed both by district health authorities and WHO as well. Factors which encourage higher immunization rates were better maternal education, presence of lady health workers in the area and nearby availability of immunization service.